Analysis Of Motor Vehicle Taxpayer Compliance In South Lampung Regency - Rizky, Naufal Dwiky Athalla; Primadona, Alsya Azzahra; Arista, Dinda Dwi; Aziziyah, Mutiara Verly; Elvandi, Ardhan Prasetya; Irawan, Andri Bagas; Kadhafi, M. Raihan Zaky; Rahmadani, Arin (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Tax is a crucial source of regional and national revenue utilized to finance public infrastructure and development. This study aims to empirically analyze the determinants of motor vehicle taxpayer compliance in South Lampung Regency. Specifically, it evaluates the effects of voice and accountability, tax system transparency, government effectiveness, and tax sanctions on compliance levels. Utilizing a quantitative approach, primary data were gathered via questionnaires from 100 motor vehicle taxpayers selected through purposive sampling within the region. The data were analyzed using multiple linear regression via EViews software, ensuring adherence to classical assumption tests to achieve the Best Linear Unbiased Estimator (BLUE). The empirical results demonstrate that voice and accountability, a transparent tax system, and tax sanctions exhibit a positive and statistically significant impact on compliance. Conversely, government effectiveness possesses a positive but statistically non-significant influence. Notably, tax sanctions emerge as the most dominant factor accelerating compliance. Simultaneously, all four independent variables significantly explain 62.49% of the variance in vehicle taxpayer compliance. These insights recommend that policymakers focus on refining enforcement mechanisms and improving systemic transparency to foster optimal local revenue generation.